Relevansi Pemikiran Pendidikan Buya Hamka dalam Penguatan Pendidikan Karakter pada Era Society 5.0 - Lukman Taufik Hidayat Susanto; Harianto Harianto; Mulyanto Abdul Khoir (Takuana: Jurnal Pendidikan, Sains, dan Humaniora, 2026)
The Society 5.0 era has intensified the need for character-based education to address moral challenges arising from rapid technological advancement. This study aims to analyze the relevance of Buya Hamka’s educational thought in strengthening character education within contemporary Islamic education. The study employed a qualitative library research approach using descriptive and analytical methods. Data were collected from Buya Hamka’s major works and relevant scholarly literature on Islamic education and character development. The findings reveal that Buya Hamka’s educational philosophy emphasizes the integration of faith, knowledge, morality, and intellectual development through the collaborative roles of parents, teachers, and society. These principles remain highly relevant for developing learners who are morally grounded, intellectually competent, and socially responsible in the Society 5.0 era. The study concludes that Buya Hamka’s educational thought offers a comprehensive conceptual foundation for strengthening character education in contemporary educational contexts.